2017
DOI: 10.1016/j.mjafi.2017.02.013
|View full text |Cite
|
Sign up to set email alerts
|

A randomized control trial to assess efficacy of Mifepristone in medical management of uterine fibroid

Abstract: Mifepristone when given in bi-weekly doses was found to be safe, efficacious, and cost effective as compared to treatment with tranexemic acid and mefenemic acid for management of fibroid uterus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 14 publications
0
17
1
Order By: Relevance
“…Recently, different administration schedules were evaluated in two Indian trials, using weekly or biweekly doses of 50 mg claiming good results 126,127. Using the vaginal route for the administration of 10 mg daily of MFP, treatment significantly reduced the volume of fibroids 128…”
Section: Selective Progesterone Receptor Modulators (Sprms)mentioning
confidence: 99%
“…Recently, different administration schedules were evaluated in two Indian trials, using weekly or biweekly doses of 50 mg claiming good results 126,127. Using the vaginal route for the administration of 10 mg daily of MFP, treatment significantly reduced the volume of fibroids 128…”
Section: Selective Progesterone Receptor Modulators (Sprms)mentioning
confidence: 99%
“…9 One more study conducted by Arora et al it was found that all patients became amenorrhic at the end of treatment, resulting in a PBAC score of "zero". 10 This concluded that mifepristone is an effective choice of treatment for fibroid and related symptoms in perimenopausal age group and in patients who want to avoid surgical treatment.…”
Section: Discussionmentioning
confidence: 95%
“…A study conducted by Arora CD et al, it was seen that with mifepristone all patients without exception had amenorrhea bringing the PBAC score to 'zero'. 17 In one more study conducted by Shradha et al, patients out of 50 became amenorrhea, and there is no patient with menorrhagia at the end of treatment. 18 Therefore, Mifepristone is a reasonable choice of treatment in perimenopausal age group and patients who want to avoid surgery.…”
Section: Discussionmentioning
confidence: 97%